On the gelation of Premna microphylla turcz extracts: The effects of supernatant and precipitate of plant ash suspension. (June 2022) - Yu, Qingqing; Xiong, Zhiyu; Shi, Tong; Yuan, Li; Bao, Yulong; Gao, Ruichang
Graphical abstract: Highlights: Fractions of plant ash (PA) varied in pH, monovalent and divalent cations. Divalent cations in plant ash induced gelation of Premna microphylla turcz (PMT). Higher concentration of plant ash weakened the gelation of PMT via increased pH. Solutions to increase safety of a traditional food production were explored. Abstract: In order to elucidate the gelling mechanism of Premna microphylla turcz (PMT) induced by plant ash (PA), PA was fractionated into supernatant (PA-S) and precipitation (PA-P) and added to the PMT suspension, respectively. The effects of different concentrations (1–9%) and fractions (PA, PA-S, PA-P) of PA suspension on the gel properties were studied. Results showed that the electrical conductivity, content of monovalent cations, pH were higher in PA-S than PA-P. Both the PA-S and PA-P fractions induced the gelation of PMT (except for the low concentration at 1% for PA-S), and the PA-P-PMT gels showed much higher gel strength and hardness than PA-S-PMT gels. With increased concentration, the gel strength increased in PA-P-PMT, but decreased in PA-S-PMT. A hypothesis for the gelation of PMT induced by PA was proposed: the divalent cations in PA bind to carboxyl group in pectin and form gels; when higher content of PA is added, a higher pH leads to extensive dissociation of carboxyl groups thereby increases the electrostatic repulsion between pectin chains, which ultimately weakens the gelling forces. This study can provide theoretical support for further optimization of the traditional processing of PMT gels.